2021
DOI: 10.21037/sci-2021-058
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in hematopoietic stem cell transplant: a systematic review of the literature

Abstract: Hematopoietic stem cell transplant (HSCT) is an expensive and complex treatment regimen that can be curative in many diseases of the bone marrow, including malignant and non-malignant conditions. The introduction of the Affordable Care Act increased access to potential candidates and removed or reduced many barriers previously identified in the literature, however, racial disparities continue to persist. As HSCT expands its utilization and indications, there is a continued need to understand the multifactorial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Published data for other populations reported that 43%–61% of patients in European countries would probably have a 10/10 MUD 7,18,19 . A higher percentage in our group is probably due to the homogeneity of the Croatian population and a lack of influence from other non‐European origin populations as opposed to other European countries or the United States 18,20,21 . An additional explanation might also lie in the fact that donors with a matching probability of <2% are not considered by our protocol and therefore not included in any further analysis.…”
Section: Discussionmentioning
confidence: 85%
“…Published data for other populations reported that 43%–61% of patients in European countries would probably have a 10/10 MUD 7,18,19 . A higher percentage in our group is probably due to the homogeneity of the Croatian population and a lack of influence from other non‐European origin populations as opposed to other European countries or the United States 18,20,21 . An additional explanation might also lie in the fact that donors with a matching probability of <2% are not considered by our protocol and therefore not included in any further analysis.…”
Section: Discussionmentioning
confidence: 85%
“…It also found racial/ethnic disparities in either OS, PFS, graft‐vs‐host disease, posttransplant relapse or transplant‐related mortality – particularly in relation to outcomes experienced by Black American patients. Although worse survival and poorer transplant outcomes were partly related to differences in human leukocyte antigen matching, donor source, disease and performance status, time to transplant, socioeconomic status, insurance status and family income disparities in outcomes generally persisted after clinical and socioeconomic factors adjustment 21 . This suggests that existing disparities, including nonreferral may relate to real and perceived racial bias and health‐related stigma.…”
Section: Race and Ethnicity In Haemopoietic Stem Cell Transplantmentioning
confidence: 99%
“…18 White patients are more often referred for transplant, more often receive stem cells from an optimally matched donor and experience improved progression-free survival (PFS) and overall survival (OS) compared with patients from ethnic minorities (non-White/Hispanic peoples). [18][19][20] A recent systematic review on racial disparities in HSCT utilisation and outcomes 21 included 40 studies (all conducted in North America), consisting of registry reviews, surveys, cohort studies and qualitative studies. This review established that there is substantial variation in access to HSCT by patients from ethnic minority groups (Black, Hispanic or Asian patients) when compared with White patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Referral rates vary based on race among various pathologies which is a contributing factor to the disparity in HSCT utilization (Caucasians: 62%, blacks: 57%, other races: 43%). 8 Bridging the gap in racial and ethnic disparities in allo-HSCT is crucial, not only to provide equity and inclusion in the utilization of this life-saving procedure but also to collect information on differences in efficacy of the procedures and frequency of complications such as graftversus-host disease (GVHD) among different races and ethnic groups. It also provides the opportunity to adequately determine the efficacy of any new medications for treating some of the complications of allo-HSCT in different racial and ethnic groups.…”
Section: Introductionmentioning
confidence: 99%